Determination of the minimal level of neutralizing antibodies elicited following vaccination able to protect rabbits against virulent cowpox virus - Mambetaliyev, Muratbay; Alieva, Alina; Abduraimov, Yergali; Rsaliyev, Aralbek; Zhugunissov, Kuandyk (Frontiers in Immunology, 2025)
BackgroundSerological assessment of antibody levels is a crucial measure of immunity in vaccinated animals. Establishing the level of antibodies considered protective is essential for vaccine standardization and evaluation of efficacy. The virus neutralization test (VNT), recognized as the gold standard for detecting virus-specific antibodies able to neutralize virus.MethodsThis study evaluated the effect of viral dose on the detection of humoral immune responses in rabbits vaccinated with a cowpox virus-based vaccine. Blood serum samples were collected on days 14, 21, and 28 post-vaccination. VNT was conducted using viral doses of 100, 50, 25, and 10 TCID50. Additionally, the infectious dose 50 (ID50) of the challenge virus was determined based on the induction of skin necrosis in 50% of infected animals. This dose (316 ID50 per 0.1 mL) was then used to challenge vaccinated rabbits in order to determine the protective antibody titer threshold.ResultsLower viral doses (25 and 10 TCID50) demonstrated higher sensitivity, with neutralizing antibody titers detected at 1:16 and above, significantly exceeding those obtained using 50 and 100 TCID50. Based on these findings, 25 TCID50 was selected as the optimal dose for future VNT. Following cowpox virus challenge, rabbits with neutralizing titers ≥1:16 were protected from skin necrosis, while non-immunized animals developed characteristic lesions.ConclusionThese results suggest that a low-dose (25 TCID50) VNT improves the sensitivity and that a titer of 1:16 can be considered a protective threshold. This approach provides a reliable laboratory model for assessing the immunogenicity and efficacy of cowpox virus vaccines. The results obtained in this study allow for an objective assessment of the immunity elicited from a cowpox vaccine using a laboratory model.